Utilização de sistemas dedicados a protocolos de rede aplicados à eficiência energética da iluminação pública - Amorim, Leonardo Gomes de Paiva (2011)
The public illumination system of Natal/RN city presents some recurring problems in the aspect of monitoring, since currently is not possible to detect in real time the light bulbs which are on throughout the day, or those which are off or burned out, at night. These factors depreciate the efficiency of the services provided, as well as, the use of energetic resources, because there is energetic waste and, consequently, financial resources that could be applied at the own public system illumination. The purpose of the work is create a prototype in substitution to the currently photoelectric relays used at public illumination, that have the same function, as well others: turn on or off the light bulbs remotely (control flexibility by the use of specifics algorithms supervisory), checking the light bulbs status (on or off) and wireless communication with the system through the ZigBee® protocol. The development steps of this product and the tests carried out are related as a way to validate and justify its use at the public illumination